Red wine consumption mitigates the cognitive impairments in low-density lipoprotein receptor knockout (LDLr−/−) mice. (2nd December 2021) - De Paula, Gabriela Cristina; de Oliveira, Jade; Engel, Daiane Fátima; Lopes, Samantha Cristiane; Moreira, Eduardo Luiz Gasnhar; Figueiredo, Claudia Pinto; Prediger, Rui Daniel; Fabro de Bem, Andreza
ABSTRACT: Although the benefits of moderate intake of red wine in decreasing incidence of cardiovascular diseases associated to hypercholesterolemia are well recognized, there are still widespread misconceptions about its effects on the hypercholesterolemia-related cognitive impairments. Herein we investigated the putative benefits of regular red wine consumption on cognitive performance of low-density lipoprotein receptor knockout (LDLr −/− ) mice, an animal model of familial hypercholesterolemia, which display cognitive impairments since early ages. The red wine was diluted into the drinking water to a final concentration of 6% ethanol and was available for 60 days for LDLr −/− mice fed a normal or high-cholesterol diet. The results indicated that moderate red wine consumption did not alter locomotor parameters and liver toxicity. Across multiple cognitive tasks evaluating spatial learning/reference memory and recognition/identification memory, hypercholesterolemic mice drinking red wine performed significantly better than water group, regardless of diet. Additionally, immunofluorescence assays indicated a reduction of astrocyte activation and lectin stain in the hippocampus of LDLr −/− mice under consumption of red wine. These findings demonstrate that the moderate consumption of red wine attenuates short- and long-term memory decline associated with hypercholesterolemia in mice and suggest that it could be through a neurovascular action.